2014
DOI: 10.1016/j.envsoft.2013.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the impact of model scale on simulated, gridded switchgrass yields

Abstract: a b s t r a c tResults of gridded ecosystem simulations of bioenergy crops are used for estimating economic viability, environmental impacts, and potential land use change. Gridded model uncertainty propagates through these uses, thus we propose a simple method for estimating regional, spatial model error from sparse field data. We apply this method to the Agricultural-BioGeochemical Cycles (Agro-BGC) model to examine and reduce the model uncertainty associated with grid scale for simulated switchgrass yields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
(104 reference statements)
0
8
0
Order By: Relevance
“…Recent studies stress that the representativeness of site‐based parameters commonly used in process‐based crop models deteriorates at larger scales [ Iizumi et al ., ]. When larger‐scale parameters are utilized in ESM‐crop model formulations, the resulting yields and outputs must be compared against values of a similar scale and bias corrected before interpretation [ Di Vittorio and Miller , ; Iizumi et al ., ]. Iizumi et al .…”
Section: Representing Agriculture Through Dynamic Coupled Climate‐crmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies stress that the representativeness of site‐based parameters commonly used in process‐based crop models deteriorates at larger scales [ Iizumi et al ., ]. When larger‐scale parameters are utilized in ESM‐crop model formulations, the resulting yields and outputs must be compared against values of a similar scale and bias corrected before interpretation [ Di Vittorio and Miller , ; Iizumi et al ., ]. Iizumi et al .…”
Section: Representing Agriculture Through Dynamic Coupled Climate‐crmentioning
confidence: 99%
“…One challenge lies specifically in the scale at which crop parameters are obtained, as a mismatch between these and ESM resolutions may compromise simulated crop growth and enhance prediction errors [Baron Journal of Advances in Modeling Earth Systems 10. 1002/2016MS000749 et al, 2005Di Vittorio and Miller, 2014;Iizumi et al, 2014]. Recent studies stress that the representativeness of site-based parameters commonly used in process-based crop models deteriorates at larger scales [Iizumi et al, 2014].…”
Section: Representing Agriculture Through Dynamic Coupled Climate-crmentioning
confidence: 99%
See 1 more Smart Citation
“…Olesen et al (2000) found that a 10 km or finer spatial resolution of input data can improve the simulation accuracy in modeling the winter wheat yields in Denmark. Mearns et al (2004) and Di Vittorio & Miller (2014) found that aggregation of weather data resulted in high uncertainty for simulation of crop yields at regional scales. Mummery & Battaglia (2002) found that by using low-resolution input data, the mean productivity for large geographic extents can be biased, especially for regions with heterogeneous soil conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent studies have highlighted large spreads in regional multi-model climate ensemble projections, at both coarse and fine resolutions (e.g., Mearns et al, 2013;Qiao et al, 2014, van der Linden andMitchell, 2009). While these differences are often attributed to model differences in general, inappropriate resolution or spatial aggregation in models can cause significant biases in outputs (Di Vittorio and Miller, 2014;Ogle et al, 2006;Riley et al, 2009). …”
Section: Introductionmentioning
confidence: 99%